Synthesis and optoelectronic properties of a Quinoxalino-Phenanthrophenazine (QPP) extended Tribenzotriquinacene (TBTQ) - Ueberricke, Lucas; Benke, Bahiru P.; Kirschbaum, Tobias; Hahn, Sebastian; Rominger, Frank; Bunz, Uwe H. F.; Mastalerz, Michael (Chemistry - a European journal, 2021)
A six-step synthesis towards a tribenzotriquinacene (TBTQ) bearing three quinoxalinophenanthrophenazine (QPP) units is presented. The optoelectronic properties are investigated and the effect of the three-dimensional arrangement of the individual QPP planes is examined using optical spectroscopy, electrochemical analysis and quantum-chemical calculations.